Ensaios em Macroeconometria - Oliveira, José Sérgio Casé de (2017)
This thesis develops three essays in macroeconometry. In the ﬁrst essay, we investigated whether the Central Bank of Brazil takes into account the stock market to determine the Selic interest rate. Based on Nisticò (2012) and Funke, Paetz e Pytlarczyk (2011), we proposed a Dynamic Stochastic General Equilibrium model (DSGE) for a small open economy with asset market, and we used Bayesian methods to estimate the parameters of this model. The results indicated that the Brazilian monetary authority responds to inﬂation and to output gap, but it does not react to stock prices. These results are in accordancetothe theoretical view,whichsaysthecentral bank shouldreactonlyindirectly to asset prices, but only when those prices imply changes in inﬂationary expectations and current inﬂation. We also observed that shocks in asset prices has little inﬂuence on macroeconomic variables. In the second essay, we investigated the determinants of the central bank independence for a set of 89 countries. As the index of the central bank independence belongs to an interval of [0,1], we used parametric and semiparametric models, which consider the limited nature of this variable. More speciﬁcally, we propose to model the central bank independence index by quantile regression using link functions based on Cauchy and Logistic distributions. Furthermore, we modeled the central bank independence index using one-inﬂated beta regression proposed by Ospina e Ferrari (2012). The results show that the participation on the European Union, and the variability of the unemployment rate, positively aﬀects the central bank independence. Moreover, political variables, such as the federalism and the democratization, can aﬀect directly the central bank independence. In the third essay, the parameters of hybrid New Keynesian Phillips Curve(NKPC)areestimatedwiththeobjectiveofevaluatingthedeterminantsofBrazilian inﬂation.Forthis,weusetechniquesderivedfromAndersoneRubin(1949),adaptedtothe MinimumDistance(MD)methodbyMagnussoneMavroeidis(2010)anditdoesn’trequire any hypothesis about the identiﬁcation. Conﬁdence sets of the hybrid CPNK structural parameters are estimated using the parametric speciﬁcation worked by Magnusson e Mavroeidis (2010). In addition, a robustness analysis of the results obtained using diﬀerent proxies for actual marginal cost is made. The results are compatible with the literature, indicating a high degree of price rigidity and a considerable degree of indexation of prices in the Brazilian economy, indicating the rejection of the hypothesis that the NKPC is purely forward-looking.